Pengaruh Media Booklet terhadap Pengetahuan Ibu pada Tumbuh Kembang Anak Prasekolah - Adjie, Dhea Firanti; Rochmawati Rochmawati (Pusat Riset dan Inovasi Nasional, 2024)
Health education is an important effort to enhance community knowledge, particularly among mothers, regarding the growth and development of preschool children. Maternal knowledge is influenced by factors such as education, access to information, socio-cultural and environmental conditions, experience, and age. Lack of knowledge may result in inadequate stimulation, which can hinder a child’s optimal development. One effective and practical educational medium to improve maternal understanding is a booklet, as it delivers information clearly, concisely, and can be reviewed repeatedly. This study aimed to determine the effect of booklet media on maternal knowledge regarding preschool children’s growth and development. The research used a quantitative approach with a quasi-experimental design, applying a one-group pre-test and post-test method. The population consisted of 77 mothers at RA/TK Islam Nurul Iman, with 43 respondents selected through convenience sampling. Data were collected using a questionnaire administered before and after the health education intervention. The results showed that the average knowledge score before the intervention was 14.58, which increased to 17.56 after the intervention, with a mean difference of 2.977. Statistical analysis produced a p-value of 0.000 (<0.05), indicating a significant effect of booklet media on maternal knowledge improvement. The study concludes that booklet media is an effective, low-cost, and practical tool for health education, helping mothers and families play an active role in supporting optimal child growth and development while serving as an alternative medium for health workers in providing educational interventions.